IPTEKS PENGUATAN BADAN PENELITIAN DAN PENGEMBANGAN DAERAH PROVINSI SULAWESI UTARA PASCA PENERAPAN PERATURAN PEMERINTAH TENTANG INOVASI DAERAH - Humiang, Faisal; Rimbing, Sheron H.R.; Sumanti, Alva O.; Pontoh, Winston (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Article 386 paragraph 1 of Law Number 23 Year 2014 concerning Regional Government which made for increasing the regional government’s performance. The innovation that took place in the city of Manado in 2016 was a successful innovation in the region. After the issuance of Government Regulation Number 38 of 2017 concerning Regional Innovation, it’s stated that regional innovation is organized by the head of the Research and Development Agency (R & D). Applying a qualitative approach through literature studies. It aims to contribute ideas about various efforts that can be done by R & D of Manado City institutions in carrying out their functions in Government Regulation Number 38 of 2017 concerning Regional Innovation. Agencies must be the organization responsible for regional innovation by providing solutions for regional innovation, becoming the Independent Team Coordinator to deal with problems that occur in these countries. Agencies must carry out additional budgets to support tasks to improve the Regional Innovation System.Keyword :Regional innovation, agency and governments.